Indonesia's Regulation Model as A Harmonization of Arrangements And Implementation Of Heirs' Approval On Asset Grants - Putri Purbasari Raharningtyas Marditi; Beatric Fortunata; Jefrianus Raga Koten (Research Collaboration Community (RCC), 2023)
Provisions on grants are regulated in Article 1666 of the Civil Code (BW), that grants are gifts by someone to another person free of charge and cannot be withdrawn, for movable goods (in front of a notary) and immovable goods (with a deed of Land Deed Official –